Cutting tool

By forming a hard particle layer composed of titanium, silicon, carbon and nitrogen on the substrate of the cutting tool, and setting a region with periodic silicon concentration changes thereon, the problem that existing cutting tools are prone to damage films under high cutting resistance conditions is solved, and a longer tool life is achieved.

CN119630499AActive Publication Date: 2025-03-14SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380054778.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-03-14
Estimated Expiration
2043-07-13

AI Technical Summary

Technical Problem

When existing cutting tools cut materials with high cutting resistance, the coating is easily damaged, resulting in a shortening of the tool life.

Method used

A cutting tool is used to arrange a hard particle layer on the substrate, wherein the hard particle layer is composed of titanium, silicon, carbon and nitrogen, including a first region and a second region, and the concentration of silicon varies periodically along the direction of the hard particle layer.

Benefits of technology

It improves the wear resistance and defect resistance of cutting tools under high cutting resistance conditions, and extends the tool life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630499A_ABST
    Figure CN119630499A_ABST
Patent Text Reader

Abstract

A cutting tool provided with a base material and a coating film disposed on the base material, the coating film comprising a hard particle layer comprising a plurality of hard particles, the plurality of hard particles comprising titanium, silicon, carbon, and nitrogen, the hard particle layer comprising a first region and a second region, the first region comprising titanium, silicon, carbon, and nitrogen, the second region comprising titanium, silicon, carbon, and nitrogen, and the second region comprising titanium, silicon, carbon, and nitrogen. The first region is sandwiched between a first main surface of the hard particle layer on the base material side and an imaginary surface S1 that is 0.5 [mu] m away from the first main surface toward the hard particle layer side. And a second region sandwiched between a second principal surface of the hard particle layer on the opposite side to the first principal surface and an imaginary plane S2 at a distance of 0.5 [mu] m from the second principal surface to the hard particle layer side, the composition of the first region being Ti (1-Xb) SiXbCN, and the composition of the second region being Ti (1-Xs) SiXsCN, xs and Xb satisfy the relationships Xs-Xb > = 0.01 and 0 < Xb < Xs < = 0.10, the hard particles have a cubic crystal structure, and the concentration of the silicon in the hard particles changes periodically in a first direction from the first principal surface toward the second principal surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to cutting tools. Background Art

[0002] Conventionally, in order to improve the wear resistance of a cutting tool, a cutting tool having a TiSiCN film formed on a substrate has been developed (for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2022 / 230363 Summary of the invention

[0006] The cutting tool disclosed herein comprises a substrate and a coating disposed on the substrate, wherein:

[0007] The coating comprises a hard particle layer,

[0008] The hard particle layer is composed of a plurality of hard particles, and the plurality of hard particles are composed of titanium, silicon, carbon and nitrogen.

[0009] The hard particle layer includes a first region and a second region.

[0010] The first region is a region sandwiched between a first main surface of the hard particle layer on the substrate side and a virtual surface S1 having a distance of 0.5 μm from the first main surface to the hard particle layer side.

[0011] The second region is a region sandwiched between a second main surface of the hard particle layer opposite to the first main surface and a virtual surface S2 with a distance of 0.5 μm from the second main surface to the hard particle layer side.

[0012] The composition of the first region is Ti (1-Xb) Si Xb CN,

[0013] The composition of the second region is Ti (1-Xs) Si Xs CN,

[0014] Xs and Xb satisfy the relationship of Xs-Xb≥0.01 and 0<Xb<Xs≤0.10,

[0015] The hard particles have a cubic crystal structure.

[0016] In the hard particles, the concentration of the silicon changes periodically along a first direction from the first main surface toward the second main surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram showing an example of a cross section of the cutting tool according to the first embodiment.

[0018] Figure 2 This is a schematic diagram showing another example of the cross section of the cutting tool according to the first embodiment.

[0019] Figure 3 This is a schematic diagram showing another example of the cross section of the cutting tool according to the first embodiment.

[0020] Figure 4 This is a schematic diagram showing another example of the cross section of the cutting tool according to the first embodiment.

[0021] Figure 5 This is a schematic diagram showing another example of the cross section of the cutting tool according to the first embodiment.

[0022] Figure 6 This is a schematic cross-sectional view of an example of a CVD apparatus used for manufacturing a cutting tool according to the second embodiment. DETAILED DESCRIPTION

[0023] [Problems to be Solved by the Present Disclosure]

[0024] The cutting tool of Patent Document 1 has a TiSiCN film with high hardness, so it has excellent wear resistance. On the other hand, when the cutting tool of Patent Document 1 is used to cut a workpiece with high cutting resistance such as FCD700 (ductile iron), the tool life may be reached due to the destruction of the film. Therefore, a cutting tool that can have a long tool life is required, especially when cutting a workpiece with high cutting resistance.

[0025] Therefore, an object of the present disclosure is to provide a cutting tool that can have a long tool life, especially when cutting a workpiece having high cutting resistance.

[0026] [Effects of the present disclosure]

[0027] According to the present disclosure, it is possible to provide a cutting tool that can have a long tool life, particularly when cutting a workpiece having high cutting resistance.

[0028] [Description of Embodiments of the Present Disclosure]

[0029] First, embodiments of the present disclosure will be described by way of examples.

[0030] (1) The cutting tool disclosed herein comprises a substrate and a coating disposed on the substrate, wherein:

[0031] The coating comprises a hard particle layer,

[0032] The hard particle layer is composed of a plurality of hard particles, and the plurality of hard particles are composed of titanium, silicon, carbon and nitrogen.

[0033] The hard particle layer includes a first region and a second region.

[0034] The first region is a region sandwiched between a first main surface of the hard particle layer on the substrate side and a virtual surface S1 having a distance of 0.5 μm from the first main surface to the hard particle layer side.

[0035] The second region is a region sandwiched between a second main surface of the hard particle layer opposite to the first main surface and a virtual surface S2 with a distance of 0.5 μm from the second main surface to the hard particle layer side.

[0036] The composition of the first region is Ti (1-Xb) Si Xb CN,

[0037] The composition of the second region is Ti (1-Xs) Si Xs CN,

[0038] Xs and Xb satisfy the relationship of Xs-Xb≥0.01 and 0<Xb<Xs≤0.10,

[0039] The hard particles have a cubic crystal structure.

[0040] In the hard particles, the concentration of the silicon changes periodically along a first direction from the first main surface toward the second main surface.

[0041] According to the present disclosure, it is possible to provide a cutting tool that can have a long tool life, particularly when cutting a workpiece having high cutting resistance.

[0042] (2) Alternatively, in the above (1), the hard particle layer has a columnar structure. Thus, the stress of the hard particle layer relative to the shear direction is strong, and the wear resistance is improved. Furthermore, since the hard particle layer has fewer grain boundaries in the direction perpendicular to the film thickness, the starting point of destruction is reduced, and the defect resistance is also improved.

[0043] (3) Alternatively, in the above (1) or (2), the ratio L1 / T1 of the length L1 of the hard particles along the first direction to the thickness T1 of the hard particle layer is 0.3 or more. As a result, the stress of the hard particle layer relative to the shear direction is strong, and the wear resistance is improved. Furthermore, since the hard particle layer has fewer grain boundaries in the direction perpendicular to the film thickness, the starting point of destruction is reduced, and the defect resistance is also improved.

[0044] (4) In any one of the above (1) to (3), the periodic width of the concentration of the silicon in the hard particles along the first direction is not less than 3 nm and not more than 20 nm. Thus, the strain in the hard particles is maintained, the progress of cracks in the coating is further suppressed, and the defect resistance of the cutting tool is further improved.

[0045] (5) In any one of (1) to (4) above, the average thickness of the hard particle layer may be 2 μm or more and 15 μm or less. This further improves the tool life.

[0046] (6) In any of the above (1) to (5),

[0047] The coating includes a base layer disposed between the substrate and the hard particle layer.

[0048] The base layer includes at least one selected from the group consisting of a TiN layer, a TiC layer, a TiCN layer, a TiBN layer, a TiCNO layer and an Al2O3 layer.

[0049] By configuring a TiN layer, a TiC layer, a TiCN layer, a TiCNO layer or a TiBN layer as a base layer, the adhesion between the substrate and the coating can be improved. In addition, by using an Al2O3 layer as a base layer, the oxidation resistance of the coating can be improved.

[0050] (7) In any of the above (1) to (6),

[0051] The coating includes a surface layer provided on the outermost surface of the coating,

[0052] The surface layer is a TiN layer or an Al2O3 layer.

[0053] This improves the heat crack resistance and wear resistance of the coating.

[0054] [Details of the embodiments of the present disclosure]

[0055] In the present disclosure, expressions in the format of “A to B” refer to the upper and lower limits of a range (i.e., greater than A and less than B). When there is no unit recorded in A and only a unit is recorded in B, the unit of A is the same as that of B.

[0056] In the present disclosure, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, all conventionally known atomic ratios are included, and the atomic ratio is not necessarily limited to the atomic ratio within the stoichiometric range.

[0057] In the present disclosure, when more than one numerical value is recorded as the lower limit and the upper limit of the numerical range, a combination of any numerical value recorded in the lower limit and any numerical value recorded in the upper limit is also disclosed. For example, when more than a1, more than b1, and more than c1 are recorded as the lower limit, and less than a2, less than b2, and less than c2 are recorded as the upper limit, more than a1 and less than a2, more than a1 and less than b2, more than a1 and less than c2, more than b1 and less than a2, more than b1 and less than b2, more than b1 and less than c2, more than c1 and less than a2, more than c1 and less than b2, more than c1 and less than c2 are disclosed.

[0058] When developing a cutting tool that can have a long tool life even when cutting a workpiece with high cutting resistance, the inventors of the present invention cut a workpiece with high cutting resistance using a conventional cutting tool and observed the damage morphology of the coating.

[0059] When cutting a workpiece with high cutting resistance using the cutting tool of Patent Document 1, it was confirmed that the load in the shear direction was large on the rake face where the chips had rubbed, and the position close to the substrate became a fulcrum and cracks occurred, thereby aggravating the destruction of the film. It is speculated that this is because the TiSiCN film has high hardness and therefore excellent wear resistance, but the toughness of the film is insufficient for cutting workpieces with high cutting resistance.

[0060] The inventor of the present invention has conducted in-depth research based on the above insights, and as a result, has obtained a cutting tool that can have a long tool life even when cutting a workpiece with high cutting resistance. Specific examples of the cutting tool disclosed in the present invention are described below with reference to the accompanying drawings. In the drawings disclosed in the present invention, the same reference numerals represent the same parts or equivalent parts. In addition, the dimensional relationships such as length, width, thickness, depth, etc. are appropriately changed for the clarity and simplification of the drawings, and do not necessarily represent the actual dimensional relationships.

[0061] [Embodiment 1: Cutting Tool]

[0062] use Figure 1 to Figure 5 A cutting tool according to one embodiment of the present disclosure (hereinafter also referred to as “this embodiment”) will be described.

[0063] The cutting tool 1 of the present embodiment includes a substrate 10 and a coating 15 disposed on the substrate 10.

[0064] The coating 15 includes a hard particle layer 11,

[0065] The hard particle layer 11 is composed of a plurality of hard particles, and the plurality of hard particles are composed of titanium, silicon, carbon and nitrogen.

[0066] The hard particle layer 11 includes a first area A1 and a second area A2.

[0067] The first region A1 is a region sandwiched between the first principal surface Q1 on the substrate 10 side of the hard particle layer 11 and a virtual surface S1 with a distance of 0.5 μm from the first principal surface Q1 to the hard particle layer 11 side.

[0068] The second region A2 is a region sandwiched between the second main surface Q2 of the hard particle layer 11 on the side opposite to the first main surface Q1 and a virtual surface S2 with a distance of 0.5 μm from the second main surface Q2 toward the hard particle layer 11.

[0069] The composition of the first region A1 is Ti (1-Xb) Si Xb CN,

[0070] The composition of the second region A2 is Ti (1-Xs) Si Xs CN,

[0071] Xs and Xb satisfy the relationship of Xs-Xb≥0.01 and 0<Xb<Xs≤0.10,

[0072] The hard particles have a cubic crystal structure.

[0073] In the hard particles, the concentration of silicon changes periodically along a first direction from the first main surface toward the second main surface.

[0074] The cutting tool of the present embodiment can have a long tool life even when cutting a workpiece with high cutting resistance. The reason for this is not clear, but it is presumed to be the following (i) to (iii).

[0075] (i) In the cutting tool of the present embodiment, the coating has a hard particle layer composed of a plurality of hard particles, and the plurality of hard particles are composed of titanium, silicon, carbon and nitrogen. The hard particle layer has high hardness. Therefore, the cutting tool having the hard particle layer has excellent wear resistance. Therefore, the cutting tool can have a longer tool life.

[0076] (ii) In the cutting tool of the present embodiment, the hard particle layer includes a first region on the substrate side and a second region on the surface side, the silicon content of the first region is less than the silicon content of the second region, and the toughness of the first region is better than that of the second region. Therefore, when the cutting tool having the hard particle layer is cutting a workpiece with high cutting resistance, the generation of cracks with the position of the hard particle layer close to the substrate as a fulcrum can be suppressed. Therefore, the cutting tool can have a longer tool life.

[0077] (iii) In the hard particles of the cutting tool of the present embodiment, the concentration of silicon changes periodically along the first direction from the first main surface of the hard particle layer toward the second main surface. Thus, even if strain is generated in the hard particles and cracks accompanying cutting are generated on the surface of the coating, the progress of the cracks to the substrate can be effectively suppressed. In addition, the hardness of the hard particles and the hard particle layer increases, and the wear resistance of the cutting tool is improved. Therefore, the cutting tool can have a longer tool life.

[0078] <Cutting tools>

[0079] like Figure 1 As shown, the cutting tool 1 of the present embodiment includes a substrate 10 and a coating 15 disposed on the substrate 10 . Figure 1 Indicates the case where the coating 15 is composed only of the hard particle layer 11. The coating 15 preferably covers at least a portion of the part of the substrate involved in cutting, and more preferably covers the entire surface of the substrate. The part of the substrate involved in cutting refers to an area on the surface of the substrate within 500 μm from the edge line of the blade tip. Even if a part of the substrate is not covered by the coating or the composition of the coating is partially different, it does not deviate from the scope of the present disclosure.

[0080] <Types of cutting tools>

[0081] The cutting tools disclosed herein may be, for example, drills, end mills (e.g., ball-end mills), indexable cutting inserts for drills, indexable cutting inserts for end mills, indexable cutting inserts for milling, indexable cutting inserts for turning, metalworking saws, gear cutting tools, reamers, taps, etc.

[0082] <Base Material>

[0083] The substrate 10 includes a rake face and a flank face, and any substrate known in the past can be used as such a substrate, for example, preferably any one of cemented carbide (for example, WC-based cemented carbide including tungsten carbide and cobalt, which may include carbonitrides of Ti, Ta, Nb, etc.), cermet (cermet with TiC, TiN, TiCN, etc. as main components), high-speed steel, ceramic (titanium carbide, silicon carbide, silicon nitride, aluminum nitride, aluminum oxide, etc.), cubic boron nitride sintered body, or diamond sintered body.

[0084] The substrate is composed of a cemented carbide containing tungsten carbide and cobalt, and the content of cobalt in the cemented carbide can be 5% by mass or more and 11% by mass or less. As a result, the balance between hardness and strength at high temperatures is excellent, and the substrate of the cutting tool for the above-mentioned purpose has excellent characteristics. When a WC-based cemented carbide is used as the substrate, its structure may contain free carbon and an abnormal layer called an η phase or an ε phase.

[0085] Furthermore, the surface of the substrate may be modified. For example, in the case of cemented carbide, a de-β layer may be formed on the surface, and in the case of cermet, a surface hardening layer may be formed. The substrate exhibits the desired effect even if its surface is modified.

[0086] In the case where the cutting tool is an indexable cutting insert, etc., the base material may or may not have a chip breaker. The shape of the cutting edge line portion may be a sharp edge (a ridge where the front cutting surface and the back cutting surface intersect), honing (rounding the sharp edge), a negative edge (chamfering), or a combination of honing and a negative edge.

[0087] <Lamination>

[0088] 《Composition of coating》

[0089] The coating of the present embodiment includes a hard particle layer. The coating of the present embodiment only needs to include a hard particle layer, and may include other layers.

[0090] For example, Figure 2 As shown in the cutting tool 1 , the coating 15 may include, in addition to the hard particle layer 11 , a base layer 12 disposed between the substrate 10 and the hard particle layer 11 .

[0091] like Figure 3 As shown in the cutting tool 1 , the coating 15 may include a surface layer 13 disposed on the hard particle layer 11 in addition to the hard particle layer 11 and the base layer 12 .

[0092] like Figure 4 As shown in the cutting tool 1 , the coating 15 may include, in addition to the hard particle layer 11 , the base layer 12 , and the surface layer 13 , an intermediate layer 14 disposed between the base layer 12 and the hard particle layer 11 .

[0093] The details of the hard granular layer, base layer, intermediate layer and surface layer will be described later.

[0094] 《Thickness of coating》

[0095] The thickness of the coating of the present embodiment may be greater than 2 μm and less than 30 μm. Here, the thickness of the coating refers to the thickness of the entire coating. If the thickness of the entire coating is greater than 3 μm, it can have excellent wear resistance. On the other hand, if the thickness of the entire coating is less than 30 μm, it can suppress the peeling or damage of the coating when a large stress is applied between the coating and the substrate during cutting. From the viewpoint of improving wear resistance, the lower limit of the thickness of the entire coating may be greater than 2 μm, or greater than 5 μm, or greater than 8 μm, or greater than 10 μm. From the viewpoint of suppressing the peeling or damage of the coating, the upper limit of the thickness of the entire coating may be less than 30 μm, or less than 25 μm, or less than 20 μm. The thickness of the entire coating may be greater than 5 μm and less than 25 μm, or greater than 8 μm and less than 20 μm.

[0096] In the present disclosure, the thickness of the coating is measured according to the following steps. The cutting tool is cut with a cross section parallel to the normal direction of the surface to obtain a measurement sample in which the cross section of the coating is exposed. The measurement sample is observed using a scanning transmission electron microscope (STEM: Scanning Transmission Electron Microscopy) to measure the thickness of the coating. The measurement sample is a thin slice sample processed using an ion slicer or the like. As a scanning transmission electron microscope, for example, JEM-2100F (trademark) manufactured by JEOL Ltd. is listed. The measurement conditions are set to an acceleration voltage of 200 kV and a current of 0.3 nA.

[0097] In the present disclosure, when "thickness" is referred to, the thickness refers to the average thickness. Specifically, the observation magnification of the measurement sample is set to 10,000 times, and a rectangular measurement field of "length parallel to the surface of the cutting tool is 100 μm" × "length including the entire thickness of the coating" is set in the electron microscope image, and the thickness width of ten locations in the field of view is measured, and the average value is set as "thickness". The thickness (average thickness) of each layer described below is also measured and calculated in the same way.

[0098] It was confirmed that, as long as the measurement was performed on the same sample, there was almost no variation in the measurement results even if the selected portion of the measurement field was changed and the measurement was performed multiple times, and the results did not change randomly even if the measurement field was set arbitrarily.

[0099] <Hard granular layer>

[0100] Composition of the hard granular layer

[0101] The hard particle layer of the present embodiment is composed of a plurality of hard particles, and the plurality of hard particles are composed of titanium, silicon, carbon and nitrogen. The hard particle layer can also be described as a TiSiCN layer composed of hard particles composed of TiSiCN. The TiSiCN layer has high hardness. Therefore, the wear resistance of the cutting tool having the TiSiCN layer is excellent. As long as the effect of the present disclosure is not impaired, the hard particle layer may also contain impurity elements while containing titanium, silicon, carbon and nitrogen. As impurity elements, chlorine, cobalt, tungsten and oxygen can be listed. The content of impurity elements in the hard particle layer can be set to, for example, less than 0.5 atomic %. The content of impurity elements in the hard particle layer is measured by EDX (Energy Dispersive X-ray Spectroscopy) (TEM-EDX) with TEM (Transmission Electron Microscopy: TEM).

[0102] like Figure 5 As shown, the hard particle layer 11 includes a first area A1 and a second area A2. The first area A1 is an area sandwiched by a first main surface Q1 on the substrate 10 side of the hard particle layer 11 and an imaginary surface S1 with a distance of 0.5 μm from the first main surface Q1 to the hard particle layer 11 side. The second area A2 is an area sandwiched by a second main surface Q2 on the side opposite to the first main surface Q1 of the hard particle layer 11 and an imaginary surface S2 with a distance of 0.5 μm from the second main surface Q2 to the hard particle layer side.

[0103] The composition of the first region is Ti (1-Xb) Si Xb CN, the composition of the second region is Ti (1-Xs) Si Xs CN. Here, Xs and Xb satisfy the relationship of Xs-Xb≥0.01 and 0<Xb<Xs≤0.10.

[0104] The lower limit of Xs-Xb is 0.01 or more, 0.02 or more, 0.03 or more, or 0.04 or more. The upper limit of Xs-Xb is 0.09 or less, 0.08 or less, or 0.07 or less. Xs-Xb can be 0.01 or more and 0.09 or less, 0.02 or more and 0.08 or less, 0.03 or more and 0.07 or less, or 0.04 or more and 0.07 or less.

[0105] The lower limit of Xb may be 0.01 or more, 0.02 or more, or 0.03 or more. The upper limit of Xb may be 0.09 or less, 0.08 or less, or 0.07 or less. Xb may be 0.01 or more and 0.09 or less, 0.02 or more and 0.08 or less, or 0.03 or more and 0.07 or less.

[0106] The lower limit of Xs may be 0.02 or more, 0.03 or more, or 0.04 or more. The upper limit of Xs may be 0.10 or less, 0.09 or less, or 0.08 or less. Xs may be 0.02 or more and 0.10 or less, 0.03 or more and 0.09 or less, or 0.04 or more and 0.08 or less.

[0107] In the present disclosure, the composition Ti of the first region (1-Xb) Si Xb CN and the second region composition Ti (1-Xs) Si Xs CN was measured according to the following procedure.

[0108] (A1) The cutting tool is cut with a diamond wire along the normal line of the surface of the cutting tool to expose the cross section of the hard particle layer. The exposed cross section is subjected to focused ion beam processing (hereinafter also referred to as "FIB processing") to make the cross section mirror-finished.

[0109] (A2) In the cross section after FIB processing, the composition is measured by line analysis along the thickness direction of the film using EDX (SEM-EDX) with SEM (Scanning Electron Microscopy). The beam diameter of the line analysis is 0.9 nm or less, the scanning interval is 50 nm, and the acceleration voltage is 15 kV. As a result of the line analysis, chlorine, tungsten, cobalt, and oxygen as impurity elements are removed, and a region A composed of titanium, silicon, carbon, and nitrogen is determined. In the above cross section, the region A is determined at three locations that do not overlap and are separated from each other by more than 1 μm. In the above cross section, the line connecting the positions of the regions A at the three locations closest to the substrate corresponds to the first main surface Q1 on the substrate side of the hard particle layer. In the above cross section, the line connecting the positions of the regions A at the three locations farthest from the substrate corresponds to the second main surface Q2 of the hard particle layer on the opposite side to the first main surface Q1. In the above cross section, the region sandwiched by the first main surface Q1 and the second main surface Q2 corresponds to the hard particle layer 11.

[0110] (A3) In the cross section after FIB processing, a first region and a second region are determined in the hard particle layer. The first region A1 is a region sandwiched by the first principal surface Q1 on the substrate 10 side of the hard particle layer 11 and the imaginary surface S1 with a distance of 0.5 μm from the first principal surface Q1 to the hard particle layer 11 side. The second region A2 is a region sandwiched by the second principal surface Q2 on the side opposite to the first principal surface Q1 of the hard particle layer 11 and the imaginary surface S2 with a distance of 0.5 μm from the second principal surface Q2 to the hard particle layer 11 side.

[0111] (A4) In the first region A1, a rectangular analysis is performed by SEM-EDX to determine the composition of the first region A1. The rectangular analysis is performed on three non-overlapping rectangular measurement areas of 0.5 μm×2 μm set in the first region A1. In the present disclosure, the average composition of the three measurement areas is equivalent to the composition Ti of the first region A1. (1-Xb) Si Xb CN. Through the above steps, Xb can be obtained.

[0112] In the second region A2, a rectangular analysis is performed by SEM-EDX to determine the composition of the second region A2. The rectangular analysis is performed on three non-overlapping rectangular measurement areas of 0.5 μm×2 μm set in the second region A2. In the present disclosure, the average composition of the measurement area at the three locations is equivalent to the composition Ti of the second region. (1-Xs) Si Xs CN. Through the above steps, Xs can be obtained.

[0113] It was confirmed that as long as the measurement was performed on the same sample, there was almost no variation in the measurement results even if the cutting position of the cutting tool and the measurement area were changed and the measurement was performed multiple times.

[0114] The hard particle layer of this embodiment may also include a third region sandwiched between the first region and the second region. The composition of the third region is not particularly limited as long as it does not impair the effect of the present disclosure. The composition of the third region may be a composition that can maintain the continuity of the organization of the hard particle layer. (1-Xm) Si Xm In CN, it was confirmed that the effect of the present disclosure is not impaired if Xb×0.9<Xm<Xs×1.1. The composition of the third region is measured by the same method as the above-mentioned method for measuring the composition of the first region.

[0115] 《Crystal Structure of Hard Particles》

[0116] In this embodiment, the hard particles have a cubic crystal structure. If the hard particles have a cubic crystal structure, both excellent wear resistance and high toughness can be achieved. The fact that the hard particles have a cubic crystal structure can be confirmed by pattern analysis based on electron diffraction with a restricted field of view.

[0117] 《Changes in silicon concentration in hard particles》

[0118] In the hard particles of the present embodiment, the concentration of silicon changes periodically along a first direction from the first main surface toward the second main surface of the hard particle layer. The fact that the concentration of silicon changes periodically along a first direction from the first main surface toward the second main surface of the hard particle layer in the hard particles can be confirmed by the following steps.

[0119] (B1) The cutting tool is cut with a diamond wire along the normal line of the surface of the cutting tool to expose the cross section of the hard particle layer. The exposed cross section is subjected to focused ion beam processing (hereinafter also referred to as "FIB processing") to make the cross section mirror-finished.

[0120] (B2) A cross section after FIB processing is observed using a bright field scanning electron microscope (BF-SEM) to identify a hard particle. Next, a BE-STEM image of the identified hard particle is obtained.

[0121] (B3) In the above BF-STEM image, the measurement region (size: 100 nm×100 nm) is set to include a region where 10 or more layers are stacked, respectively, in white and black. The layers in black are regions with a high silicon content, and the layers in white are regions with a low silicon content.

[0122] (B4) Determine the stacking direction of the layer represented by white (hereinafter, also referred to as "white layer") and the layer represented by black (hereinafter, also referred to as "black layer") in the measurement area in the above BF-STEM image. Specifically, the stacking orientation of the white layer and the black layer is overlapped with the electron beam diffraction pattern of the limited field of view, and the stacking orientation is determined based on the orientation shown by the diffraction spot.

[0123] (B5) In the measurement area in the above BF-STEM image, the composition is measured by line analysis along the stacking direction using EDX (Energy Dispersive X-ray Spectroscopy) with STEM. The beam diameter of the line analysis is less than 0.5 nm, the scanning interval is 0.5 nm, and the length of the line analysis is 50 nm.

[0124] (B6) Create a graph showing the results of the line analysis in a coordinate system in which the X axis represents the distance from the measurement start point and the Y axis represents the number of silicon atoms A.Si Relative to the atomic number of titanium A Ti The atomic number of silicon is A Si The percentage of the total Si / (A Ti +A Si )}×100. In this graph, {A Si / (A Ti +A Si )}×100 (hereinafter also referred to as “average”). As the distance from the measurement start point increases, the Si / (A Ti +A Si )} large area and {A Si / (A Ti +A Si )} When the regions with large and small sizes alternately exist, it is confirmed that the concentration of silicon in the hard particles changes periodically along the first direction from the first main surface toward the second main surface of the hard particle layer.

[0125] It was confirmed that, as long as the measurement was performed on the same sample, even if the hard particles determined in the above (B2) were changed and the measurement was performed a plurality of times, there was almost no variation in the measurement results.

[0126] 《Periodic width of silicon concentration in hard particles》

[0127] In the hard particles of the present embodiment, the periodic width of the silicon concentration along the first direction from the first main surface toward the second main surface of the hard particle layer can be greater than 3nm and less than 20nm. Thus, the strain in the hard particles is maintained, the progress of cracks is further suppressed in the coating, and the defect resistance of the cutting tool is further improved. The periodic width of the silicon concentration can be greater than 3nm and less than 15nm, or can also be greater than 5nm and less than 10nm.

[0128] In the present disclosure, the method for measuring the period width of the silicon concentration is as follows. The measurement area is set by the same method as (B1) to (B3) above. The measurement area is Fourier transformed to obtain a Fourier transformed image. In the Fourier transformed image, the periodicity in the measurement area is expressed as a point. The period width is calculated by calculating the inverse of the distance between the point and the center of the image representing the maximum intensity in the Fourier transformed image.

[0129] It was confirmed that as long as the measurement was performed on the same sample, there was almost no variation in the measurement results even if the measurement site was changed and the measurement was performed multiple times.

[0130] The organization of the hard granular layer

[0131] The hard particle layer of this embodiment can be a columnar structure. Thus, the stress of the hard particle layer relative to the shear direction is strong, and the wear resistance is improved. Further, since the hard particle layer has few grain boundaries in the direction perpendicular to the film thickness, the starting point of destruction decreases, and the defect resistance is also improved.

[0132] In the present disclosure, the hard particle layer having a columnar structure means that the percentage (N1 / N)×100 of the number N1 of first hard particles having an aspect ratio of 3 or more relative to the number N of all hard particles constituting the hard particle layer is 50% or more. Specifically, the fact that the hard particle layer has a columnar structure is confirmed by the following steps.

[0133] (C1) The cutting tool is cut with a diamond wire along the normal line of the surface of the cutting tool to expose the cross section of the hard particle layer, and the exposed cross section is subjected to focused ion beam processing (hereinafter also referred to as "FIB processing") to make the cross section mirror-finished.

[0134] (C2) Using a field emission scanning electron microscope (FE-SEM) (product name: "SUPRA35VP", manufactured by Carl Zeiss) equipped with an electron backscatter diffraction device (EBSD device), EBSD analysis is performed on the cross-section after FIB processing under the following measurement conditions. The area for EBSD analysis (hereinafter also referred to as the analysis area) is a rectangular area set in three non-overlapping locations within the hard particle layer. The size of the analysis area is a rectangle with a length of more than 20 μm in the direction parallel to the substrate. The length of the analysis area in the thickness direction of the coating can be appropriately set according to the thickness of the hard particle layer. The length of the analysis area in the thickness direction of the coating is set to, for example, more than 90% of the thickness of the hard particle layer.

[0135] (Measurement conditions)

[0136] Accelerating voltage: 15 kV

[0137] Current value: 1.8nA

[0138] Irradiation current: 60μm (with HC)

[0139] Exp: Long 0.03s

[0140] Binning: 8×8

[0141] WD: 15mm

[0142] Tilt: 70°

[0143] Step size: 0.02μm

[0144] BKD: Background Subtraction,

[0145] Dynamic Background Subtraction,

[0146] Normalize Intensity histogram

[0147] Shooting magnification: 20000 times

[0148] Grain boundary definition: 15° or more

[0149] (C3) For the data collected by EBSD analysis, only the data satisfying CI>0.1 are identified by CIDilation method (singleInteration) and Grain CI Standardization, thereby performing a cleanup process. The CI value is calculated by the Voting method. Specifically, it is obtained by CI=(V1-V2) / Videal (V1, V2: the first and second solutions, Videal: the ideal solution).

[0150] (C4) The EBSD analysis results were analyzed using commercially available software (trade name: "OIM7.1", manufactured by TSL Solutions Co., Ltd.), and an IPF map (Inverse Pole Tigre map) of the analysis area was prepared. In the preparation of the IPF map, the case where the orientation difference angle of adjacent measurement points is 15° or more is defined as a grain boundary. The shape of each grain is shown in the IPF map, and the orientation of each grain is shown in a color-coded manner.

[0151] (C5) Using the above-mentioned software ("OMI7.1"), the aspect ratio of all hard particles in the IPF diagram of each analysis area is measured respectively. The aspect ratio of hard particles refers to the ratio b / a of the major diameter a to the minor diameter b of the hard particles. In the present disclosure, the major diameter a is the maximum span diameter of the hard particles observed in the above-mentioned section, and the minor diameter b is the maximum diameter of the hard particles along the direction orthogonal to the major diameter a. In the present disclosure, the hard particles in the IPF diagram of the analysis area include both hard particles that are all present in the IPF diagram of the analysis area and hard particles that are at least partially present in the IPF diagram of the analysis area.

[0152] (C6) Calculate the percentage (n1 / n)×100 of the number n1 of first hard particles having an aspect ratio of 3 or more relative to the number n of all hard particles in the IPF diagram of each analysis area. In the present disclosure, the average of the percentage (n1 / n)×100 in the IPF diagram of the analysis area of ​​three locations is equivalent to the percentage (N1 / N)×100 of the number N1 of first hard particles having an aspect ratio of 3 or more relative to the number N of all hard particles constituting the hard particle layer. When the percentage (N1 / N)×100 is 50% or more, it is confirmed that the hard particle layer has a columnar structure.

[0153] It was confirmed that as long as the measurement was performed on the same sample, there was almost no variation in the measurement results even if the cutting position of the cutting tool and the measurement area were changed and the measurement was performed multiple times.

[0154] In the hard particle layer of the present embodiment, the lower limit of the percentage (N1 / N)×100 may be 60% or more, 70% or more, 80% or more, or 90% or more. The upper limit of the percentage (N1 / N)×100 may be, for example, 100% or less. The percentage (N1 / N)×100 may be 60% or more and 100% or less, 70% or more and 100% or less, 80% or more and 100% or less, or 90% or more and 100% or less.

[0155] In this embodiment, the ratio L / T of the length L of the hard particles along the first direction to the thickness T of the hard particle layer can be 0.3 or more. As a result, the stress of the hard particle layer relative to the shear direction is strong, and the wear resistance is improved. Furthermore, since the hard particle layer has fewer grain boundaries in the direction perpendicular to the film thickness, the starting point of the destruction becomes less, and the defect resistance is also improved.

[0156] In the present embodiment, from the viewpoint of improving wear resistance and defect resistance, the lower limit of the ratio L / T may be 0.4 or more, 0.5 or more, or 0.6 or more. The upper limit of the ratio L / T may be 1.0 or less, or 0.9 or less. The lower limit of the ratio L / T may be 0.3 or more and 1.0 or less, 0.4 or more and 1.0 or less, 0.5 or more and 0.9 or less, or 0.6 or more and 0.9 or less.

[0157] In the present disclosure, the thickness T of the hard particle layer and the length L of the hard particles along the first direction are measured according to the following procedure.

[0158] (D1) An IPF map of the analysis area is prepared in the same steps as steps (C1) to (C4) of the above-mentioned method for confirming that the hard particle layer is a columnar structure. In this step, the analysis area in (C1) is a rectangular area of ​​"a length parallel to the surface of the cutting tool of 100 μm" x "a length including the entire thickness of the coating" at three non-overlapping locations.

[0159] (D2) Using software ("OMI7.1"), in the IPF diagram of each analysis area, the thickness amplitude of ten locations is measured along the first direction from the first main surface toward the second main surface of the hard particle layer, and the average value t thereof is calculated. The first direction is perpendicular to the first main surface of the hard particle layer. In the present disclosure, the average of the average values ​​t of the analysis areas of the three locations is equivalent to the thickness T of the hard particle layer.

[0160] (D3) Using software ("OMI7.1"), the lengths of all hard particles in the IPF diagram of each analysis area along the first direction are measured, and the average value L1 thereof is calculated. In the present disclosure, the hard particles in the IPF diagram of the analysis area include both hard particles that are all present in the IPF diagram of the analysis area and hard particles that at least a portion of the hard particles are present in the measurement area. In the present disclosure, the average of the average values ​​L1 of the analysis areas at the three locations is equivalent to the length L of the hard particles along the first direction.

[0161] It was confirmed that as long as the measurement was performed on the same sample, there was almost no variation in the measurement results even if the cutting position of the cutting tool and the measurement area were changed and the measurement was performed multiple times.

[0162] 《Thickness of the hard granular layer》

[0163] The thickness of the hard particle layer of the present embodiment may be greater than 2 μm and less than 15 μm. If the thickness of the hard particle layer is greater than 2 μm, it can have excellent wear resistance. On the other hand, if the thickness of the hard particle layer is less than 15 μm, it is possible to suppress the peeling or damage of the coating when a large stress is applied between the coating and the substrate during cutting. From the viewpoint of improving wear resistance, the lower limit of the thickness of the hard particle layer may be greater than 4 μm, may be greater than 6 μm, or may be greater than 8 μm. From the viewpoint of suppressing the peeling or damage of the coating, the upper limit of the thickness of the hard particle layer may be less than 15 μm, or may be less than 10 μm. The thickness of the hard particle layer may be greater than 4 μm and less than 15 μm, or may be greater than 6 μm and less than 10 μm.

[0164] <Base layer>

[0165] The coating of Embodiment 1 may include a base layer disposed between the substrate and the hard particle layer. The base layer may include at least one selected from the group consisting of a TiN layer, a TiC layer, a TiCN layer, a TiBN layer, a TiCNO layer, and an Al2O3 layer.

[0166] As the base layer, by configuring a TiN layer, a TiC layer, a TiCN layer, a TiCNO layer or a TiBN layer just above the base, the close contact between the base and the coating can be improved. By using an Al2O3 layer as the base layer, the oxidation resistance of the coating can be improved. The average thickness of the base layer can be greater than 0.1 μm and less than 20 μm. As a result, the coating can have excellent wear resistance and defect resistance.

[0167] <Surface layer>

[0168] The coating of embodiment 1 may include a surface layer disposed on the outermost surface of the coating. The surface layer may be a TiN layer or an Al2O3 layer. The color of the TiN layer is clear (golden), so if it is used as a surface layer, it has the advantage of easy identification of the corners of the cutting blade after cutting (identification of the used part). By using the Al2O3 layer as the surface layer, the oxidation resistance of the coating can be improved.

[0169] The average thickness of the surface layer may be 0.5 μm or more and 10 μm or less. This improves the adhesion between the surface layer and the adjacent layer.

[0170] <Middle Layer>

[0171] The coating of embodiment 1 may include an intermediate layer disposed between the base layer and the hard particle layer. When the base layer is a TiN layer, the intermediate layer is preferably a TiCN layer. Since the TiCN layer has excellent wear resistance, appropriate wear resistance can be imparted by the coating. The average thickness of the intermediate layer may be greater than 1 μm and less than 20 μm.

[0172] [Embodiment 2: Method for manufacturing cutting tool]

[0173] An example of a method for manufacturing a cutting tool according to Embodiment 1 will be described. The method for manufacturing a cutting tool according to Embodiment 1 may include a first step of preparing a substrate and a second step of forming a coating on the substrate to obtain a cutting tool.

[0174] <First step>

[0175] In the first step, a substrate is prepared. The details of the substrate are described in Embodiment 1, and therefore the description thereof will not be repeated.

[0176] <Second step>

[0177] Next, in the second step, a coating is formed on the substrate to obtain a cutting tool. The coating is formed, for example, using Figure 6 In the CVD device 50, a plurality of substrate placement jigs 52 holding the substrate 10 can be provided, and these are covered by a reaction vessel 53 made of a heat-resistant alloy. In addition, a temperature control device 54 is arranged around the reaction vessel 53, and the temperature in the reaction vessel 53 can be controlled by the temperature control device 54.

[0178] The CVD device 50 is provided with a nozzle 56 having three inlet ports 55 and 57 (another inlet port is not shown). The nozzle 56 is arranged so as to penetrate the region where the substrate installation jig 52 is arranged. A plurality of injection holes (a first injection hole 61, a second injection hole 62, and a third injection hole (not shown)) are formed in a portion of the nozzle 56 near the substrate installation jig 52.

[0179] exist Figure 6 In the embodiment, the gases introduced into the nozzle 56 from the inlet 55, the inlet 57 and another inlet (not shown) are not mixed in the nozzle 56, but are introduced into the reaction container 53 through different injection holes. The nozzle 56 can rotate with its axis as the central axis. In addition, the CVD device 50 is provided with an exhaust pipe 59, and the exhaust gas can be discharged to the outside from the exhaust port 60 of the exhaust pipe 59. In addition, the jigs and the like in the reaction container 53 are usually made of graphite.

[0180] When the coating film includes at least one of a base layer, an intermediate layer, and a surface layer, these layers can be formed by a conventionally known method.

[0181] As raw material gas, TiCl4, SiCl4 and CH3CN are used. TiCl4 is ejected from a plurality of first injection holes provided in the nozzle, SiCl4 is ejected from a plurality of second injection holes provided in the nozzle, and CH3CN is ejected from a plurality of third injection holes provided in the nozzle. Specifically, TiCl4 is introduced into the nozzle 56 from the inlet 55 of the nozzle and ejected from a plurality of first injection holes 61. SiCl4 is introduced into the nozzle 56 from the inlet 57 of the nozzle and ejected from a plurality of second injection holes 62. CH3CN is introduced into the nozzle 56 from the inlet (not shown) of the nozzle and ejected from a plurality of third injection holes (not shown). As a carrier gas, H2 gas, N2 gas, Ar gas, etc. can be used. In the present disclosure, a gas containing a raw material gas and a carrier gas is referred to as a reaction gas.

[0182] When forming the hard particle layer, the following conditions (i) and (ii) are adopted.

[0183] (i) Vary the percentage (V1 / V)×100 of the volume flow rate V1 of CH3CN with respect to the overall volume flow rate V of the reaction gas. For example, during the period from the start to the end of the formation of the hard particle layer, gradually increase the percentage (V1 / V)×100.

[0184] (ii) Vary the flow rate V of SiCl4 Si with respect to the total flow rate V of TiCl4 and SiCl4 Ti+Si by the percentage (V Si / V Ti+Si )×100. For example, during the period from the start to the end of the formation of the hard particle layer, increase the percentage (V Si / V Ti+Si )×100.

[0185] By adopting the above conditions (i) and (ii), the composition of the first region and the second region of the hard particle layer can be changed. In the composition Ti (1-Xb) Si Xb CN of the first region and the composition Ti (1-Xs) Si Xs CN of the second region, it can be adjusted so that Xs and Xb satisfy the relationship of Xs - Xb ≥ 0.01 and 0 < Xb < Xs ≤ 0.10.

[0186] When forming the hard particle layer, in order to adjust so that in the composition Ti (1-Xb) Si Xb CN of the first region and the composition Ti (1-Xs) Si Xs CN of the second region, Xs and Xb satisfy the relationship of Xs - Xb ≥ 0.01 and 0 < Xb < Xs ≤ 0.10, it is also effective to increase the substrate temperature. In particular, in the composition Ti (1-Xb) Si Xb CN of the first region and the composition Ti (1-Xs) Si Xs CN of the second region, in order to set Xb to 0.07 or more and Xs to 0.09 or more, it is effective to increase the substrate temperature when forming the hard particle layer.

[0187] When forming the hard particle layer, form the film while rotating the nozzle. As a result, in the hard particles, the concentration of silicon varies periodically along the growth direction of the hard particle layer.

[0188] In this process, the substrate temperature in the reaction container is 800°C to 900°C, and the pressure in the reaction container is 50hPa to 300hPa. The thickness of the hard particle layer can be controlled by adjusting the flow rate of the raw material gas and the film formation time. The cycle width of the silicon concentration in the hard particles can be controlled by adjusting the rotation speed of the nozzle and the film formation time.

[0189] In the formation of the hard particle layer, the total gas flow rate of the reaction gas can be set to 70L / min to 90L / min, for example. Here, "total gas flow rate" means the total volume flow rate of the gas under standard conditions (0°C, 1 atmosphere) as an ideal gas introduced into the CVD furnace per unit time.

[0190] (Other processes)

[0191] Next, the substrate 10 on which the coating is formed is cooled. The cooling rate does not exceed 5° C. / min, for example, and the cooling rate becomes slower as the temperature of the substrate 10 decreases.

[0192] In addition to the above-mentioned steps, a heat treatment step such as annealing, a surface treatment step such as surface grinding, shot peening, etc. may be performed.

[0193] The cutting tool according to the first embodiment can be obtained by the above-mentioned manufacturing method.

[0194] Example

[0195] This embodiment will be described in more detail by way of examples, but this embodiment is not limited to these examples.

[0196] <Preparation of base material>

[0197] As a substrate, a substrate made of cemented carbide was prepared. The composition of the substrate was Co: 6 mass %, NbC: 1.5 mass %, and the balance was WC. The shape of the substrate was CNMG120408N-GZ (indexable cutting insert manufactured by Sumitomo Electric Hardmetal Co., Ltd.).

[0198] <Film Formation>

[0199] A coating was formed on the surface of the substrate by CVD. The composition of the coating of each sample and the average thickness of each layer are shown in Table 1, Table 2, and Table 3. The column indicated by "-" in the table indicates that the layer does not exist.

[0200] Table 1

[0201]

[0202] Table 2

[0203]

[0204] Table 3

[0205]

[0206] The base layer (TiN layer), the intermediate layer (TiCN layer), and the surface layer (Al 2 O 3 layer) shown in the table are layers formed by a conventionally known CVD method.

[0207] Regarding the hard particle layer of each sample shown in the table, Figure 6 The CVD device shown forms a hard particle layer. The nozzle of the CVD device is provided with a first injection hole, a second injection hole and a third injection hole. In each sample, the nozzle rotation speed, substrate temperature and pressure when forming the hard particle layer are shown in Table 4, Table 5 and Table 6.

[0208] Table 4

[0209]

[0210] Table 5

[0211]

[0212] Table 6

[0213]

[0214] In samples 1 to 39, the percentage (V1 / V)×100 of the volume flow rate V1 of CH3CN relative to the volume flow rate V of the entire reaction gas was gradually increased from the start to the end of the formation of the hard particle layer. The change of the percentage (V1 / V)×100 is shown in Tables 4, 5, and 6. For example, in sample 1, the percentage (V1 / V)×100 was gradually increased from 0.4% to 0.5%.

[0215] In samples 101 to 109, the percentage (V1 / V)×100 was maintained constant during the formation of the hard particle layer. The percentage (V1 / V)×100 is shown in Tables 4, 5, and 6. For example, in sample 101, the percentage (V1 / V)×100 was maintained at 0.4%.

[0216] In samples 1 to 39, the flow rate V of SiCl4 was set to 1.5 V from the start to the end of the formation of the hard particle layer. Si Relative to the total flow rate V of TiCl4 and SiCl4 Ti+Si The percentage (V Si / V Ti+Si )×100 increases. Percentage (V Si / V Ti+Si)×100 are shown in Tables 4, 5, and 6. For example, in Sample 1, the percentage (V Si / V Ti+Si )×100 increased from 20% to 25%.

[0217] In samples 101 to 109, during the formation of the hard particle layer, the percentage (V Si / V Ti+Si )×100 is maintained constant. Percentage (V Si / V Ti+Si )×100 as shown in Tables 4, 5, and 6. For example, in Sample 101, the percentage (V Si / V Ti+Si )×100 is maintained at 20%.

[0218] In Sample 17 and Samples 29 to 39, the substrate temperature was increased during the formation of the hard particle layer. The changes in the substrate temperature are shown in Tables 5 and 6. For example, in Sample 17, the substrate temperature was increased from 850° C. to 870° C. In the other samples, the substrate temperature was maintained constant during the formation of the hard particle layer.

[0219] Thereafter, the substrate was cooled to obtain a cutting tool of each sample.

[0220] <Composition of the hard granular layer>

[0221] When the hard particle layer of the cutting tool of each sample was observed using a bright field scanning electron microscope (BF-SEM), it was confirmed that the hard particle layer was composed of a plurality of hard particles.

[0222] <Composition of the hard granular layer>

[0223] In the cutting tool of each sample, the composition Ti of the first region of the hard particle layer was determined by SEM-EDX. (1-Xb) Si Xb CN and the second region composition Ti (1-Xs) Si Xs CN was measured. The specific measurement method is as described in Embodiment 1. Based on the obtained results, Xb, Xs and Xs-Xb are shown in Tables 7, 8 and 9.

[0224] <Crystal Structure of Hard Particles>

[0225] In the hard particle layer of the cutting tool of each sample, the crystal structure of the hard particles was confirmed by pattern analysis based on electron beam diffraction with limited field of view. The results are shown in Table 7, Table 8 and Table 9. In the table, "cubic crystal" means that the hard particles are cubic crystal structures. In the table, "cubic crystal + amorphous" means that the hard particles contain cubic crystal structures and amorphous.

[0226] <Changes in Silicon Concentration in Hard Particles>

[0227] In the hard particles of the cutting tool of each sample, it was confirmed that the concentration of silicon changes along the first direction from the first main surface of the hard particle layer toward the second main surface. In the hard particles of all samples, it was confirmed that the concentration of silicon changes periodically along the first direction from the first main surface of the hard particle layer toward the second main surface.

[0228] <Cycle Width of Silicon Concentration in Hard Particles>

[0229] In the hard particles of the cutting tool of each sample, the cycle width of the silicon concentration along the first direction from the first main surface to the second main surface of the hard particle layer was measured. The specific measurement method is as described in Implementation 1. The results are shown in Tables 7, 8, and 9 under "Si concentration cycle width".

[0230] <Organization of the hard granular layer>

[0231] In the hard particle layer of the cutting tool of each sample, the percentage (N1 / N) × 100 of the number N1 of first hard particles having an aspect ratio of 3 or more relative to the number N of all hard particles constituting the hard particle layer was measured. The specific measurement method is as described in Embodiment 1. The results are shown in Tables 7, 8, and 9.

[0232] When the value of the percentage (N1 / N)×100 of each sample was 50% or more, it was determined that the hard particle layer had a columnar structure.

[0233] <l t>

[0234] In the cutting tool of each sample, the ratio L / T of the length L of the hard particles along the first direction to the thickness T of the hard particle layer was measured. The specific measurement method is as described in Embodiment 1. The results are shown in Tables 7, 8, and 9.

[0235] Table 7

[0236]

[0237] Table 8

[0238]

[0239] Table 9

[0240]

[0241] <Cutting Test 1>

[0242] Cutting was performed using cutting tools of samples 1 to 15 and samples 101 to 103 under the following cutting conditions, and the cutting time until the flank wear reached 0.2 mm was measured. The longer the cutting time, the longer the tool life. The results are shown in Table 10.

[0243] <Cutting conditions>

[0244] Cutting material: FCD700 round bar

[0245] Holder: DCNL2525M12 (manufactured by Sumitomo Electric Hardmetal Co., Ltd.)

[0246] Insert: CNMG120408N-GZ

[0247] Cutting speed Vc: 100m / min

[0248] Feed f: 0.3mm / rev

[0249] Cutting depth ap: 1.5mm

[0250] Cutting fluid: Yes (wet type)

[0251] Table 10

[0252]

[0253] <Evaluation>

[0254] The cutting tools of samples 1 to 15 correspond to the examples. The cutting tools of samples 101 to 103 correspond to the comparative examples. It was confirmed that the cutting tools of samples 1 to 15 have a longer tool life than the cutting tools of samples 101 to 103 when cutting a workpiece with high cutting resistance.

[0255] <Cutting Test 2>

[0256] Cutting was performed using cutting tools of samples 16 to 27 and 104 to 106 under the following cutting conditions, and the cutting time until the flank wear reached 0.2 mm was measured. The longer the cutting time, the longer the tool life. The results are shown in Table 11.

[0257] <Cutting conditions>

[0258] Cutting material: FCD700 round bar

[0259] Holder: DCNL2525M12 (manufactured by Sumitomo Electric Hardmetal Co., Ltd.)

[0260] Insert: CNMG120408N-GZ

[0261] Cutting speed Vc: 140m / min

[0262] Feed f: 0.3mm / rev

[0263] Cutting depth ap: 1.5mm

[0264] Cutting fluid: Yes (wet type)

[0265] Table 11

[0266]

[0267] <Evaluation>

[0268] The cutting tools of samples 16 to 27 correspond to the examples. The cutting tools of samples 104 to 106 correspond to the comparative examples. It was confirmed that the cutting tools of samples 16 to 27 have a longer tool life than the cutting tools of samples 104 to 106 when cutting a workpiece with high cutting resistance.

[0269] <Cutting Test 3>

[0270] Cutting was performed using cutting tools of samples 28 to 39 and 107 to 109 under the following cutting conditions, and the cutting time until the flank wear reached 0.2 mm was measured. The longer the cutting time, the longer the tool life. The results are shown in Table 12.

[0271] <Cutting conditions>

[0272] Cutting material: FCD700 round bar

[0273] Holder: DCNL2525M12 (manufactured by Sumitomo Electric Hardmetal Co., Ltd.)

[0274] Insert: CNMG120408N-GZ

[0275] Cutting speed Vc: 180m / min

[0276] Feed f: 0.3mm / rev

[0277] Cutting depth ap: 1.5mm

[0278] Cutting fluid: Yes (wet type)

[0279] Table 12

[0280]

[0281] <Evaluation>

[0282] The cutting tools of samples 28 to 39 correspond to the examples. The cutting tools of samples 107 to 109 correspond to the comparative examples. It was confirmed that the cutting tools of samples 28 to 39 have a longer tool life than the cutting tools of samples 107 to 109 when cutting a workpiece with high cutting resistance.

[0283] As mentioned above, although the embodiment and the example of this disclosure were described, it is also planned from the beginning that the configurations of each embodiment and the example described above are appropriately combined or variously modified.

[0284] The embodiments and examples disclosed herein are illustrative in all aspects and are not restrictive. The scope of the present invention is indicated by the claims rather than the embodiments and is intended to include all modifications within the scope and meaning equivalent to the claims.

[0285] Description of Reference Numerals

[0286] 1: cutting tool; 10: substrate; 11: hard particle layer; 12: base layer; 13: surface layer; 14: intermediate layer; 15: coating; 50: CVD device; 52: substrate setting fixture; 53: reaction container; 54: temperature control device; 55, 57: inlet; 56: nozzle; 59: exhaust pipe; 60: exhaust port; 61: first injection hole; 62: second injection hole; A1: first area; A2: second area; S1, S2: imaginary surfaces.< / l>

Claims

1. A cutting tool comprising a substrate and a coating disposed on the substrate, wherein: The coating comprises a hard particle layer, The hard particle layer is composed of a plurality of hard particles, and the plurality of hard particles are composed of titanium, silicon, carbon and nitrogen. The hard particle layer includes a first region and a second region. The first region is a region sandwiched between a first main surface of the hard particle layer on the substrate side and a virtual surface S1 having a distance of 0.5 μm from the first main surface to the hard particle layer side. The second region is a region sandwiched between a second main surface of the hard particle layer opposite to the first main surface and a virtual surface S2 with a distance of 0.5 μm from the second main surface to the hard particle layer side. The composition of the first region is Ti (1-Xb) Si Xb CN, The composition of the second region is Ti (1-Xs) Si Xs CN, Xs and Xb satisfy the relationship of Xs-Xb≥0.01 and 0<Xb<Xs≤0.10, The hard particles have a cubic crystal structure. In the hard particles, the concentration of the silicon changes periodically along a first direction from the first main surface toward the second main surface.

2. The cutting tool according to claim 1, wherein: The hard particle layer is a columnar structure.

3. The cutting tool according to claim 2, wherein: A ratio L1 / T1 of the length L1 of the hard particles along the first direction to the thickness T1 of the hard particle layer is 0.3 or more.

4. The cutting tool according to any one of claims 1 to 3, wherein: A period width of the concentration of the silicon in the hard particles along the first direction is greater than or equal to 3 nm and less than or equal to 20 nm.

5. The cutting tool according to any one of claims 1 to 4, wherein: The average thickness of the hard particle layer is 2 μm or more and 15 μm or less.

6. The cutting tool according to any one of claims 1 to 5, wherein: The coating includes a base layer disposed between the substrate and the hard particle layer. The base layer includes at least one selected from the group consisting of a TiN layer, a TiC layer, a TiCN layer, a TiBN layer, a TiCNO layer and an Al2O3 layer.

7. The cutting tool according to any one of claims 1 to 6, wherein: The coating includes a surface layer provided on the outermost surface of the coating, The surface layer is a TiN layer or an Al2O3 layer.

Citation Information

Patent Citations

  • Cemented carbide cutting tool for multi-component coating

    CN101407905A

  • Surface-coated cutting tool and manufacturing method therefor

    CN107530785A

  • Double-structure coating tool

    CN110468387A

  • Cutting tool

    CN116249599A

  • Surface-coated cutting tool having hard coating layer exhibiting superior chipping resistance

    JP2011218541A